2021
DOI: 10.1016/j.omtm.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of miPSC/mESC-derived retinal ganglion cells into healthy and glaucomatous retinas

Abstract: Optic neuropathies, including glaucoma, are a group of neurodegenerative diseases, characterized by the progressive loss of retinal ganglion cells (RGCs), leading to irreversible vision loss. While previous studies demonstrated the potential to replace RGCs with primary neurons from developing mouse retinas, their use is limited clinically. We demonstrate successful transplantation of mouse induced pluripotent stem cell (miPSC)/mouse embryonic stem cell (mESC)-derived RGCs into healthy and glaucomatous mouse r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 77 publications
1
39
0
Order By: Relevance
“…Furthermore, RGCs survive poorly in organoids during prolonged culture [60], presumably due to the absence of retrograde trophic support from the CNS, which may limit their potential to generate large numbers of RGCs without additional modifications. Guided RGC subtype specifi-cation, which has been described in both two-dimensional and organoid cultures [61,62], would allow for a more refined approach to future stem cell-based treatments.…”
Section: Donor Cell Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, RGCs survive poorly in organoids during prolonged culture [60], presumably due to the absence of retrograde trophic support from the CNS, which may limit their potential to generate large numbers of RGCs without additional modifications. Guided RGC subtype specifi-cation, which has been described in both two-dimensional and organoid cultures [61,62], would allow for a more refined approach to future stem cell-based treatments.…”
Section: Donor Cell Sourcementioning
confidence: 99%
“…In contrast, most transplanted RGCs do not exhibit distant axon extensions [34,71,74], possibly because they do not localize to the inner retinal parenchyma. Only a subset of published transplantation studies report evidence of donor cell neuritogenesis [32,33,62,70,73,74], and even fewer have described dendritic lamination into the host IPL [32,62]. In light of this, maintaining the ILM as a neuritogenic signal and growth substrate may be important, and enzymatic digestion or mechanical peeling to encourage RGC somas to enter the retinal parenchyma may actually undermine subsequent steps in neural integration [160].…”
Section: Assessing Donor Rgc Neurite Localizationmentioning
confidence: 99%
“…Thus, currently, in most research into cell replacement, the transplanted cells are initially induced into a specific cell lineage in vitro and are then transplanted for RGC replacement. The main types of transplanted cell include primary RGC [22,23], ESC-derived neural progenitor cells [36], the iPSC-derived RGC [37], RGC precursors derived from Müller cells [38], and RGC derived from spermatogonial stem cells [39].…”
Section: Stem Cell Transplantation and Replacementmentioning
confidence: 99%
“…Most of the above studies did not describe the survival rate of transplanted cells in the host retina, the distribution of transplanted cells and the evaluable transplantation success rate. Recently, Oswald et al [37] used a survival rate of >5% after donor cell transplantation as the indicator for a successful transplant and found that the miPSC/mESC-derived donor RGCs can survive for up to 12 months after transplantation with a success rate of over 65%, which is far higher than the 10% success rate of primary RGCs transplantation [22,23]. In addition, researchers have also carried out RGCs replacement research in some non-human primates.…”
Section: Stem Cell Transplantation and Replacementmentioning
confidence: 99%
“…Though RGC transplantation lags behind, owing to the complex cytoarchitecture and spatially intimidating neural connectivity that must be attained, 47 it is conceivable that even RGC replacement may one day be achieved. [48][49][50] Transdifferentiation involves induced reversion of endogenous retinal cells into a progenitor state, which may then proliferate and differentiate into retinal neurons. Varying degrees of spontaneous retinal regeneration in amphibians, teleost fish, and young avians have prompted investigations into why this capacity has been lost in mammals.…”
mentioning
confidence: 99%